A low-cost tin-containing titanium-manganese alloy and preparation method thereof

By adopting low -cost tin titanium manganese alloys, the powder metallurgical process is used to prepare, it solves the problem of poor performance in strength and plasticity in existing titanium manganese alloy, and realizes high -strength, good plasticity and high density titanium alloy preparation. , Reduce production costs.

CN116770128BActive Publication Date: 2025-01-24CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310720475.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2025-01-24
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

The existing powder metallurgical titanium-manganese alloys have poor performance in terms of strength and plasticity, which is difficult to meet the requirements of market application, and the preparation process is costly and difficult to process.

Method used

Using low cost contains tin titanium manganese alloys, according to the quality percentage of quality, TI: 88-96 %, Mn: 2 to 6 %, SN: 2 to 6 %, prepare through the powder metallurgical process, including the name of raw material powder, uniformity Mixed, suppressed and vacuum sintering.

Benefits of technology

The prepared titanium alloy has high strength, good plasticity and high density, with a tensile strength of 790-902MPa, an elongation of 6.5-16.1%, and a density of 98.6-99.6%. It also reduces production costs and improves commercial competition. force.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116770128B_ABST
    Figure CN116770128B_ABST
Patent Text Reader

Abstract

The invention discloses a low-cost tin-containing titanium-manganese alloy and a preparation method thereof, comprising: weighing raw material powders of Ti: 88-96%, Mn: 2-6%, Sn: 2-6% by mass percentage; mixing the raw material powders under a protective atmosphere to obtain a uniform mixed powder; pressing the mixed powder into a blank, and vacuum sintering to prepare a titanium alloy. The low-cost tin-containing titanium-manganese alloy provided by the invention has a small amount of alloy elements added, which is easy to control and low in price. The alloy does not require any heat treatment process, which significantly reduces the production cost. The prepared tin-containing titanium-manganese alloy has the advantages of high strength, good plasticity and high density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder metallurgy, and in particular relates to a low-cost tin-titanium-manganese alloy and a preparation method thereof. Background Art

[0002] Titanium is a lightweight, high-strength metal with excellent corrosion resistance and biocompatibility. Pure titanium and Ti-6Al-4V alloy are widely used in clinical medicine, but the mechanical properties of pure titanium are low and cannot meet the level required by biomedicine. Ti-6Al-4V alloy can cause health problems during use (slowly releasing Al ions and V ions). In order to solve this problem, people have developed various new non-toxic β-type titanium alloys in recent years, such as Ti-Ta, Ti-Nb and Ti-Zr. The addition of these expensive, high-melting-point alloying elements not only improves the biocompatibility of titanium alloys, but also greatly increases the cost and processing difficulty of the alloy, making it unable to compete with current commercial alloys. Compared with Ta, Nb and Zr elements, Mn and Sn elements with lower melting points and lower prices are more attractive.

[0003] At present, the preparation of titanium alloys mainly adopts the ingot metallurgical process. The manufacture of Ti alloy components using the traditional ingot processing route usually involves a complex processing sequence, including multiple vacuum remelting of Ti and alloy addition, homogenization, hot deformation and annealing, which leads to a significant increase in cost. The large amount of material waste during the processing further increases the cost of the component. Powder metallurgy, as a near-net shaping process, is a promising cost-effective method for manufacturing high-quality titanium alloy components with complex geometries. Due to the simple operation and simple tools required, this technology can significantly reduce material waste and reduce overall processing costs.

[0004] However, experiments have shown that although powder metallurgy titanium-manganese (Ti-Mn) alloys have good strength, they have poor plasticity and density and are difficult to meet the requirements of market applications. Therefore, providing a low-cost titanium-manganese alloy with good plasticity and a method for rapidly sintering it has become a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] One of the objects of the present invention is to provide a low-cost tin-containing titanium-manganese alloy which is a titanium alloy with high strength, good plasticity and high density.

[0008] To solve the above technical problems, the present invention provides the following technical solution: a low-cost tin-containing titanium-manganese alloy, which is composed of the following components by mass percentage: Ti: 88-96%, Mn: 2-6%, Sn: 2-6%.

[0009] As a preferred solution of the low-cost tin-titanium-manganese alloy of the present invention, the alloy has the following characteristics:

[0010] (a) Tensile strength is 790-902 MPa;

[0011] (b) elongation of 6.5 to 16.3%;

[0012] (c) Density is 98.6-99.6%.

[0013] As a preferred solution of the low-cost tin-containing titanium-manganese alloy of the present invention, it is composed of the following components by mass percentage: Ti: 6%, Mn: 2%, Sn: 2%.

[0014] Another object of the present invention is to provide a method for preparing a low-cost tin-titanium-manganese alloy, comprising:

[0015] Weigh the raw material powder according to the mass percentage as mentioned above;

[0016] Mixing the raw material powders under a protective atmosphere to obtain a uniform mixed powder;

[0017] The mixed powder is pressed into a billet and then vacuum sintered to prepare a titanium alloy.

[0018] As a preferred solution of the method for preparing the low-cost tin-titanium-manganese alloy of the present invention, the raw material powders are Ti powder, Mn powder and Sn powder, and the purity of the raw materials is ≥99.7wt%.

[0019] As a preferred solution of the method for preparing the low-cost tin-titanium-manganese alloy of the present invention, the average particle size of the raw material powder is 40 to 60 microns.

[0020] As a preferred solution of the method for preparing the low-cost tin-titanium-manganese alloy of the present invention, the protective gas is argon, the mixing speed is 100-300 r / min, and the mixing time is 20-60 min.

[0021] As a preferred solution of the method for preparing the low-cost tin-titanium-manganese alloy of the present invention, wherein: the pressing pressure for forming the billet is 500-700 MPa.

[0022] As a preferred solution of the low-cost tin-titanium-manganese alloy preparation method of the present invention, the vacuum sintering is carried out by heating the temperature to 600°C at a heating rate of 10°C / min, keeping the temperature for 60 minutes, then heating the temperature to 1100-1300°C at a heating rate of 5°C / min, and keeping the temperature for 1-3 hours.

[0023] As a preferred solution of the method for preparing a low-cost tin-titanium-manganese alloy according to the present invention, the vacuum sintering is performed at a vacuum degree of 10 -2 ~10 -3 Pa.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The low-cost tin-containing titanium-manganese alloy provided by the present invention generates a partial liquid phase during the sintering process by adding a small amount of low-melting-point elements, such as Mn and Sn, to promote the diffusion of elements during the sintering process, reduce the sintering temperature, and reduce the sintering time, thereby preparing a high-strength, good-plasticity and high-density titanium alloy. The prepared titanium alloy has a tensile strength of 790-902MPa, an elongation of 6.5-16.1%, and a density of 98.6-99.6%. The low-cost tin-containing titanium-manganese alloy provided by the present invention has a small amount of alloy elements added, which is easy to control and low in price. In addition, the alloy does not require any heat treatment process, which significantly reduces production costs and improves commercial competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0027] Figure 1 The XRD patterns of Examples 2 and 3 of the present invention and Comparative Examples 1 and 3 are shown.

[0028] Figure 2 These are backscatter scans of Examples 2 and 3 of the present invention and Comparative Examples 1 and 3, where a, b, c, and d correspond to Comparative Example 1, Example 2, Comparative Example 3, and Example 3, respectively.

[0029] Figure 3 1 and 2 are tensile stress-strain curves of Examples 2 and 3 of the present invention and Comparative Examples 1 and 3. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] Unless otherwise specified, the raw materials used in the examples were purchased commercially.

[0034] Example 1

[0035] (1) Pure titanium powder (325 mesh), pure manganese powder (400 mesh), and pure tin powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 96%, Mn is 2%, and Sn is 2%. The raw materials are weighed;

[0036] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0037] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 ~10 -3 Pa, heated to 600°C at a heating rate of 10°C / min, kept at that temperature for 60min, then heated to 1200°C at a heating rate of 5°C / min, kept at that temperature for 1h, and cooled with the furnace to obtain a tin-containing titanium-manganese alloy.

[0038] After testing, the Ti-2Mn-2Sn alloy obtained in this embodiment has a porosity of 1.4%, a yield strength of 775±4 MPa, and an elongation of 16.3±0.4%.

[0039] Example 2

[0040] (1) Pure titanium powder (325 mesh), pure manganese powder (400 mesh), and pure tin powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 96%, Mn is 2%, and Sn is 2%. The raw materials are weighed;

[0041] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0042] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 ~10 -3 Pa, heated to 600°C at a heating rate of 10°C / min, kept at that temperature for 60min, then heated to 1200°C at a heating rate of 5°C / min, kept at that temperature for 2h, and cooled with the furnace to obtain a tin-containing titanium-manganese alloy.

[0043] After testing, the Ti-2Mn-2Sn alloy obtained in this embodiment has a porosity of 1.2%, a yield strength of 784±6 MPa, and an elongation of 15.9±0.4%.

[0044] Example 3

[0045] (1) Pure titanium powder (325 mesh), pure manganese powder (400 mesh), and pure tin powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 94%, Mn is 4%, and Sn is 2%. The raw materials are weighed;

[0046] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0047] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 -10 -3 Pa, heated to 600°C at a heating rate of 10°C / min, kept at that temperature for 60min, then heated to 1200°C at a heating rate of 5°C / min, kept at that temperature for 2h, and cooled with the furnace to obtain a tin-containing titanium-manganese alloy.

[0048] After testing, the Ti-4Mn-2Sn alloy obtained in this embodiment has a porosity of 1.3%, a yield strength of 888±14 MPa, and an elongation of 6.1±0.4%.

[0049] Example 4

[0050] (1) Pure titanium powder (325 mesh), pure manganese powder (400 mesh), and pure tin powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 96%, Mn is 2%, and Sn is 2%. The raw materials are weighed;

[0051] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0052] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 ~10 -3 Pa, heated to 600°C at a heating rate of 10°C / min, kept at that temperature for 60min, then heated to 1200°C at a heating rate of 5°C / min, kept at that temperature for 0.5h, and cooled with the furnace to obtain a tin-containing titanium-manganese alloy.

[0053] After testing, the Ti-2Mn-2Sn alloy obtained in this embodiment has a porosity of 2.3%, a yield strength of 704±6 MPa, and an elongation of 8.9±0.4%.

[0054] Example 5

[0055] (1) Pure titanium powder (325 mesh), pure manganese powder (400 mesh), and pure tin powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 96%, Mn is 2%, and Sn is 2%. The raw materials are weighed;

[0056] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0057] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 ~10 -3 Pa, heated to 600°C at a heating rate of 10°C / min, kept at that temperature for 60min, then heated to 1200°C at a heating rate of 5°C / min, kept at that temperature for 3h, and cooled with the furnace to obtain a tin-containing titanium-manganese alloy.

[0058] After testing, the Ti-2Mn-2Sn alloy obtained in this embodiment has a porosity of 1.0%, a yield strength of 804±6 MPa, and an elongation of 9.1±0.5%.

[0059] Comparative Example 1

[0060] (1) Pure titanium powder (325 mesh) and pure manganese powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 98%, Mn is 2%. The raw materials are weighed;

[0061] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0062] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 -10 -3 Pa, heat to 600°C at a heating rate of 10°C / min, keep warm for 60min, then heat to 1200°C at a heating rate of 5°C / min, keep warm for 2h, and cool with the furnace to obtain titanium-manganese alloy.

[0063] After testing, the Ti-2Mn alloy obtained in this comparative example has a porosity of 1.8%, a yield strength of 695±5 MPa, and an elongation of 3.6±0.4%.

[0064] Comparative Example 2

[0065] (1) Pure titanium powder (325 mesh) and pure manganese powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 98%, Mn is 2%. The raw materials are weighed;

[0066] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0067] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 -10 -3 Pa, heat to 600°C at a heating rate of 10°C / min, keep warm for 60min, then heat to 1250°C at a heating rate of 5°C / min, keep warm for 2h, and cool with the furnace to obtain titanium-manganese alloy.

[0068] After testing, the Ti-2Mn alloy obtained in this comparative example has a porosity of 1.4%, a yield strength of 787±9 MPa, and an elongation of 5.8±0.3%.

[0069] Comparative Example 3

[0070] (1) Pure titanium powder (325 mesh) and pure manganese powder (400 mesh) are used as raw materials. The purity of each raw material is greater than 99.7%. The specific composition by mass percentage is as follows: Ti is 96% and Mn is 4%. The raw materials are weighed;

[0071] (2) adding the raw material powder into a powder mixer and mixing under an argon atmosphere at a mixing speed of 200 r / min for a mixing time of 30 min to obtain a uniform mixed powder;

[0072] (3) The mixed powder was pressed into a blank using a hydraulic press at a pressing pressure of 600 MPa and sintered in a vacuum sintering furnace with a vacuum degree of 10 -2 -10 -3 Pa, heat to 600°C at a heating rate of 10°C / min, keep warm for 60min, then heat to 1250°C at a heating rate of 5°C / min, keep warm for 2h, and cool with the furnace to obtain titanium-manganese alloy.

[0073] After testing, the Ti-4Mn alloy obtained in this comparative example has a porosity of 0.4%, a yield strength of 930±12 MPa, and an elongation of 2.1±0.3%.

[0074] The XRD patterns of Examples 2, 3 and Comparative Examples 1, 3 are as follows: Figure 1 As shown, it can be seen that with the addition of Sn, the content of β phase increases.

[0075] The backscattering scanning images of Examples 2 and 3 and Comparative Examples 1 and 3 are as follows: Figure 2 As shown, a, b, c, and d correspond to Comparative Example 1, Example 2, Comparative Example 3, and Example 3, respectively. It can be seen that for the Ti-2Mn alloy, the addition of Sn can refine the width of the phase, and the addition of Sn element to the Ti-4Mn alloy will coarsen the β phase.

[0076] The tensile stress-strain curves of Examples 2 and 3 and Comparative Examples 1 and 3 are as follows: Figure 3 shown.

[0077] The Ti-2Mn alloys in Comparative Examples 1 and 2 can only be homogenized after sintering at 1250°C for 2 hours, while Example 1 with the addition of Sn element can be completely homogenized after sintering at 1200°C for 1 hour, which reduces the sintering temperature and shortens the sintering time.

[0078] In addition, compared with comparative examples 1 and 2, the plasticity of embodiments 1 to 5 is greatly improved, and the elongation of embodiment 1 reaches 16%, which has better commercial competitiveness.

[0079] Comparative Example 4

[0080] In Comparative Example 4, based on Example 1, the mass percentages are adjusted to: Ti is 97%, Mn is 1%, and Sn is 2%. Other steps and conditions are the same as those in Example 1. Experiments have found that the solid solution strengthening effect of the obtained tin-titanium-manganese alloy is deteriorated and the strength of the alloy is reduced.

[0081] Comparative Example 5

[0082] The average particle size of the raw material powder is adjusted to be greater than 60 microns. Experiments have found that larger powder particle sizes have smaller specific surface area, lower surface energy, and lower degree of densification, resulting in poor plasticity of the alloy.

[0083] The average particle size of the raw material powder is adjusted to be less than 40 microns. Experiments have found that finer powders are more expensive and have poorer formability during pressing.

[0084] The low-cost tin-containing titanium-manganese alloy provided by the present invention generates a partial liquid phase during the sintering process by adding a small amount of low-melting-point elements, such as Mn and Sn, to promote the diffusion of elements in the sintering process, reduce the sintering temperature, and shorten the sintering time, thereby preparing a titanium alloy with high strength, good plasticity, and high density. The prepared titanium alloy has a tensile strength of 790 to 902 MPa, an elongation of 6.5 to 16.1%, and a density of 98.6 to 99.6%.

[0085] The low-cost tin-titanium-manganese alloy provided by the present invention has a small amount of alloy elements added, which is easy to control and has a low price. In addition, the alloy does not require any heat treatment process, which significantly reduces production costs and improves commercial competitiveness.

[0086] The invention provides a method for preparing a tin-titanium-manganese alloy with low cost. The powder metallurgy process can not only flexibly adjust the alloy composition and achieve extremely high utilization rate of raw materials, but also has a simple process and less subsequent machining, thereby further reducing production costs and facilitating industrial mass production.

[0087] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A low-cost tin-containing titanium-manganese alloy, characterized in that: By mass percentage, it is composed of the following components: Ti: 96%, Mn: 2%, Sn: 2%; Mixing the raw material powders under a protective atmosphere to obtain a uniform mixed powder; The mixed powder is pressed into a billet and then vacuum sintered to prepare a titanium alloy; The vacuum sintering is carried out by heating the temperature to 600°C at a heating rate of 10°C / min, keeping the temperature for 60 min, and then heating the temperature to 1200°C at a heating rate of 5°C / min, keeping the temperature for 1-2 h.

2. The low-cost tin-containing titanium-manganese alloy according to claim 1, characterized in that: The alloy has the following characteristics: (a) Tensile strength is 775-784 MPa; (b) elongation is 15.9-16.3%; (c) Density is 98.6~98.8%.

3. The low-cost tin-containing titanium-manganese alloy according to claim 1, characterized in that: The raw material powders are Ti powder, Mn powder and Sn powder, and the purity of the raw materials is ≥99.7 wt%.

4. The low-cost tin-containing titanium-manganese alloy according to claim 1, characterized in that: The average particle size of the raw material powder is 40 to 60 microns.

5. The low-cost tin-containing titanium-manganese alloy according to claim 1, characterized in that: The protective atmosphere is argon, the mixing speed is 100-300 r / min, and the mixing time is 20-60 min.

6. The low-cost tin-containing titanium-manganese alloy according to claim 1, characterized in that: The compacting process is performed under a pressing pressure of 500-700 MPa.

7. The low-cost tin-containing titanium-manganese alloy according to claim 1, characterized in that: The vacuum sintering has a vacuum degree of 10 -2 ~10 -3 Pa.

Citation Information

Patent Citations

  • Titanium base materials

    GB882463A